Tumor Viruses and Their Associated Cancers: Remain on the Track with the Latest Advances - Hassan, Sherif T S (Viruses, 2022)
Infection with certain types of deoxyribonucleic acid (DNA) or ribonucleic acid (RNA) viruses, known as tumor viruses or oncogenic viruses, can lead to cancer [...].
Keywords: Host-Pathogen Interactions; Oncogenic Viruses; Humans; Tumor Virus Infections; lidé; onkogenní viry; infekce onkogenními viry; Neoplasms; Animals; interakce hostitele a patogenu; nádory; zvířata